FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM LQ45 BEI : KOMISARIS INDEPENDEN, PROFIT MARGIN, RETURN ON EQUITY,: PRICE TO BOOK VALUE DAN PRICE TO EARNING RATIO (PERIODE 2010 - 2014) - 1, Silverawati; Kennedy, Posma Sariguna Johnson; Lumbantoruan, Rutman (Universitas Kristen Indonesia, 2017)
The aim of this research is analyze the influence partially or simultaneously between corporate governance measured with proportion of Independent Commissioners (KI) and costs of financial, measured by ratio of Profit Margin (PM), Return on Equity (ROE), Price to Book value (PBV) and Price to Earning Ratio (PER) to return. As well as analyzing the variables the dominant influence on the company under common back ILQ-45 in BEI. Data used from official sites of BEI, www.idx.com. Sample election is LQ-45 in the period 2010 - 2014. The research methods use multiple linear regression analysis. Correlation coefficient values indicate a strong enough relationship. Results of regression analysis showed that operates simultaneously, KI, PM, ROE, PER and PBV against return under common significant influence. Partially, only variables KI and PBV have the significant effect against return under common control. While variable PM, ROE and PER have no effect. The Results The result showed that the company management need to increase the role of the Independent Commissioner.Keywords: return, independent commisioner, financial ratios.